Mobile Application Characteristics and User Perspective in Smart Healthcare Service Applications - Ni Ketut Dewi Ari Jayanti; Evi Triandini; Gde Sastrawangsa; Ni Wayan Deriani (Bina Nusantara University, 2022)
The current COVID-19 pandemic has an impact on accelerating the digital transformation of various sectors in Indonesia, one of which is the health sector. Hence, many mobile applications of smart healthcare service have been developed, which can be a solution for people to get better health services. The aim of the research is to evaluate the mobile application (SpeedId and SpeedQ) for smart healthcare service based on the user perspective and the characteristics of the mobile application. The research is an analytic observational study that contains five stages of research. There are 64 respondents in the research using a questionnaire as data collection tool. Then, through a literature review, seven variables are determined, and a research model is proposed. The evaluation of the mobile application characteristics includes the operating system and network availability as independent variables and response time, responsiveness, and interface accessibility as dependent variables. Meanwhile, evaluating user perspective consists of respondents’ gender and education as independent variables and duration and ease of use as dependent variables. From the mobile application characteristics, the results show that operating system and network availability do not significantly affect all dependent variables. From the user perspective, gender only significantly affects the duration variable. Meanwhile, education significantly impacts the duration and the ease of use.